KAHOOT IN AN EFL CLASSROOM: TEACHERS’ BELIEFS - Muhammad Yoga Fadhilah; Praditya Putri Utami; Yuna Tresna Wahyuna (PROJECT (Professional Journal of English Education), 2023)
The popularity of using technology in education is growing as the educational system quickly transforms because of the pandemic conditions that exist today. Kahoot is one example of a learning platform designed to assist language teachers in the classroom. Theoretically, teachers beliefs have a big impact on how successfully classroom practices are produced. The purpose of this study is to explore teachers beliefs of using Kahoot in EFL classroom. This study employs a case study methodology. Participants in this study were two teachers with different levels of teaching experience from different vocational schools in Karawang. The data were collected through observation and interview. The study findings showed that there were three sources of teacher beliefs of using kahoot in EFL classroom, there are experience as language learners, teaching experience of what works best, and principles based on education or research. Furthermore, it was also found that teachers' beliefs in using kahoot in EFL classroom. The teachers believe that using Kahoot is influence to their teaching and learning activities, helpful for both teachers and students, and challenging to use. Keywords:  Teachers Beliefs; Kahoot; EFL Classroom